Using Artificial Intelligence to Combat Social Media Scams in Thailand - Cheepphitaksakul, Voravit (Digital Repository of Theses, 2026)
Social media scams have become a major threat in Thailand, targeting individuals and businesses through fraudulent messages, fake advertisements, and impersonation schemes. Traditional scam detection methods struggle to keep up with the rapid evolution of these deceptive tactics. This research proposes an AI-driven approach to detect and prevent social media scams in real-time. We develop a Thai-language scam detection model using WangchanBERTa, a BERT-based NLP model trained on a labeled dataset of scam-related content. The model is deployed as an API using FastAPI via A web dashboard. This AI-powered solution enhances cybersecurity efforts, providing an efficient and scalable defense against social media scams in Thailand